KAJIAN MA’ANIL HADIS TENTANG PEREMPUAN BEPERGIAN TANPA DIDAMPINGI MAHRAM - Isnaini Isnaini (Hikmah: Journal of Islamic Studies, 2021)
Abstract The study aims to convey the meaning contained in the hadith on a woman travels without accompanied by a mahram. The research is quite interesting to study recently, particularly concerning the relevance of the early fuqaha's understanding of the hadith with recent cases. This article describes some hadith explaining the prohibition to woman travels without accompanied by a mahram. Nevertheless, the hadith is implemented in the contemporary era, which commonly known as the millennial era. If the hadith were understood textually and carelessly, it would understand that all hadith has been attached nasakh by the period and place. However, it needs to reconsider why the hadith about women travels without accompanied by mahram emerges. From the review in this article, it is found that Rasulullah states the prohibition for a woman to travel without accompanied by a mahram. The prohibition was influenced by many factors, such as safety, chastity, and the situation was rather hostile for a woman at the time. Abstrak Penelitian ini bertujuan untuk mengungkap makna yang terkandung dalam hadis tentang perempuan bepergian tanpa mahram. Kajian ini cukup menarik dibahas dewasa ini, terutama terkait relevansi pemahaman para fuqaha’ terdahulu tentang hadis tersebut dengan kasus-kasus yang muncul belakangan. Dalam artikel ini diuraikan tentang sejumlah hadis yang menjelaskan tentang larangan perempuan bepergian dengan tidak ditemani mahram. Bagaiamana hadis-hadis tersebut diterapkan dalam era kontemporer ini yang sering disebuat era millennial. Kalau semua hadis itu dipahami secara tekstual dan tergesa-gesa maka akan muncul pengertian bahwa semua hadis itu telah dinasakh oleh zaman dan tempat. Namun perlu direnungkan kembali kenapa Hadis tentang perempuan bepergian tanpa mahram itu muncul. Dari kajian dalam artikel ini ditemukan bahwa Rasulullah menyatakan ketidakbolehan seorang perempuan melakukan perjalanan seorang diri tanpa mahram. Larangan ini dipengaruhi faktor keamanan, kesucian dan ketidakberpihakan keadaan saat itu pada perempuan.